Produksi Glukosamin melalui Hidrolisis Kitosan Menggunakan Irradiasi Microwave - Nur Rokhati; Titik Istirokhatun; Reisa Novita Marpaung; Ananda Dwi Utomo (Seminar Nasional Teknik Kimia Kejuangan, 2017)
Glucosamine (2-amino-2-deoxy-glucose) is an amino-monosaccharide from chitosan, which has many usesin the field of health, especially for the joints, bones, and teeth. Glucosamine can be obtained by the completehydrolysis of chitosan. The influence of microwave irradiation on the chitosan hydrolysis with catalyzed byhydrochloric acid was studied. The hydrolyzed chitosan was characterized by reducing sugar measurement,and FT-IR analysis. The results were compared between hydrolysis using conventional heating andmicrowave irradiation. Microwave irradiation can increase the reaction rate of glucosamine formation.Under the condition of microwave irradiation, the yield of glucosamine is 72.67% after 20 min hydrolysis.While to obtain yield glucosamine 70% required 2 hours for hydrolysis using conventional heating.Chemical structure by FTIR and the reducing sugar content of the glucosamine produced not different withthe glucosamine purchased from Sigma-Aldrich.